Impact of Fadama- II Project on Income Inequality and Poverty Reduction of Rural Households in Nigeria (2012)
Efforts to reduce rural inequality and poverty in Nigeria have no appreciable impact partly due to their supply-driven approach. In recent times emphasis is shifting to demand driven approach through Community Driven Development (CDD) projects with focus on bottom-up development. Fadama-II (2004 and 2009), one of the CDD projects invested mainly in agricultural assets to increase the income of the users. However, the impact of the project on Income Inequality (IE) and poverty has not been fully established. Therefore, the impact of Fadama-II on IE and poverty reduction of rural households in Nigeria was investigated. Secondary data collected by the International Food Policy Research Institute from twelve World Bank supported Fadama-II states in 2006/2007 farming year were used. These states lie in three agroecological zones; three in Humid Forest (HF), three in Moist Savanna (MS) and six in Dry Savanna (DS). A sample of 3,750 households comprising: Fadama-II Beneficiaries (FB)-34%; Fadama-II non-beneficiaries within Fadama Local Government Areas (LGAs)-33%; and Fadama-II non-beneficiaries outside Fadama LGAs-33% was used for the study. Information used was on socio-economic characteristics, major assets and major components of household income and expenditure. The data were analysed using propensity score matching, descriptive statistics, double difference estimator, Gini-coefficient, Foster-Greer-Thorbecke weighted poverty index, and Poverty Equivalent Growth Rate (PEGR) at p=0.05 There were 1738 households with similar characteristics across the strata. Mean age (42.7 ± 11.8years) and household size (9.0 ± 6.4) of FB were not significantly different from those of the non-beneficiaries. The Per Capita Expenditure (PCE) of FB before the project was N52,703.4 ± 91,730.3. Annual PCE increased by 13.8%, 17.1% and 29.1% for HF, MS and DS zones respectively. Income inequality of FB before the project was 0.547. Fadama- II decreased IE nationwide by 21.2% with female FB having higher reduction of 27.2% compared with male of 14.1%. Income inequality of FB engaged in Up- stream Farming Activities (UFA) decreased by 19.6%, while those in Down-stream Farming Activities (DFA) decreased by 10.1%. The IE reduced by 28.4%, 12.9% and 11.7% in HF, MS and DS respectively. At a poverty line of N35,299.0 per annum, 52.2% of FB were poor before the project. Poverty Incidence (PI) reduced by 34.0% for female FB compared with 7.8% for male. The poverty incidence of FB in UFA reduced by 14.2% compared with 7.1% for those in DFA. The PI reduced by 31.8%, 7.9% and 5.6% for HF, MS and DS zones respectively. The annual growth rate of PCE of 27.7% was less than the PEGR of 45.3% for FB nationwide. The PCE growth rate of 13.8%, 17.1% and 29.1% in HF, MS and DS respectively was less than their PEGR at 48.7%, 41.0%, and 39.3% respectively. Fadama-II significantly increased income and reduced both income inequality and poverty of beneficiaries especially among females across the three agroecological zones. The project benefited a larger percentage of the poor. Hence, Economic Community Driven Development projects should be encouraged to reduce income inequality and poverty in rural Nigeria.